2008
DOI: 10.5194/acp-8-2841-2008
|View full text |Cite
|
Sign up to set email alerts
|

Utilising shade to optimize UV exposure for vitamin D

Abstract: Abstract. Numerous studies have stated that humans need to utilise full sun radiation, at certain times of the day, to assist the body in synthesising the required levels of vitamin D 3 . The time needed to be spent in the full sun depends on a number of factors, for example, age, skin type, latitude, solar zenith angle. Current Australian guidelines suggest exposure to approximately 1/6 to 1/3 of a minimum erythemal dose (MED), depending on age, would be appropriate to provide adequate vitamin D 3 levels. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Advice is corrected for shade use (based on solar zenith angle: <50°=50 % reduction in vitamin D; 50°–60°=25 %; >60°=12 %) [61], but not for sunscreen use because studies of sunscreen in practice have indicated it does not affect vitamin D levels [6264]. While there is controversy over vitamin D [6573], this advice shows users that a short sun exposure during the mid- and low-latitude summers would produce adequate vitamin D without risking sunburn [57, 74] and encourages them to balance vitamin D synthesis with the risks of skin damage.…”
Section: Functions and Features Of Solar Cell Mobile Applicationmentioning
confidence: 99%
“…Advice is corrected for shade use (based on solar zenith angle: <50°=50 % reduction in vitamin D; 50°–60°=25 %; >60°=12 %) [61], but not for sunscreen use because studies of sunscreen in practice have indicated it does not affect vitamin D levels [6264]. While there is controversy over vitamin D [6573], this advice shows users that a short sun exposure during the mid- and low-latitude summers would produce adequate vitamin D without risking sunburn [57, 74] and encourages them to balance vitamin D synthesis with the risks of skin damage.…”
Section: Functions and Features Of Solar Cell Mobile Applicationmentioning
confidence: 99%
“…Utilizing shade: Shaded environments may also be utilized for sun exposure without experiencing the high levels of UVA of full sun 75 76 . At 27.6° S (Australia), diffuse UV under shade has been proved to be capable of providing the human body with adequate levels of UVD3 (290-315 nm) radiation 77 78 .…”
Section: Nutrition–ecological Transitionmentioning
confidence: 99%
“…Although global solar UV radiation is frequently registered at many radiometric stations worldwide, its diffuse fraction is scarcely measured, and therefore, information about the direct‐to‐diffuse partitioning is usually unavailable. To our knowledge, only few studies have reported experimental solar UV diffuse measurements [ Parisi et al ., , ; Grant and Gao , ; Utrillas et al ., , ; Utrillas , ; Turnbull et al ., ; Turnbull and Parisi , ; Nuñez et al ., ].…”
Section: Introductionmentioning
confidence: 99%